Monetary policy and household loan supply: Volume and composition effects - Gyîozîo Gyöngyösi; Steven Ongena; Ibolya Schindele (Magyar Nemzeti Bank, 2022)
We study how monetary conditions change the supply by banks of mortgage credit to households. We exploit the widespread presence of foreign currency mortgages in Hungary and study this country's comprehensive credit registry. Changes in monetary conditions not only affect the supply of credit in volume, but also in its currency and risk composition. Hence, we establish a "bank-lending-to-households" channel of monetary policy that is heterogeneous. While the availability of foreign currency mortgages weakens the domestic bank-lending channel overall, weakly capitalized domestic banks relying on swap transactions for their foreign currency lending are more sensitive to changes in monetary conditions.
Keywords: E51; F3; G21; 330; Bank balance-sheet channel; household lending; monetary policy; foreign currency lending